2009
DOI: 10.1038/jcbfm.2009.46
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Neutralization of the NLRP1 Inflammasome Reduces the Innate Immune Response and Improves Histopathology after Traumatic Brain Injury

Abstract: Traumatic brain injury elicits acute inflammation that in turn exacerbates primary brain damage. A crucial part of innate immunity in the immune privileged central nervous system involves production of proinflammatory cytokines mediated by inflammasome signaling. Here, we show that the nucleotide-binding, leucine-rich repeat pyrin domain containing protein 1 (NLRP1) inflammasome consisting of NLRP1, caspase-1, caspase-11, apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
292
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 293 publications
(309 citation statements)
references
References 42 publications
16
292
1
Order By: Relevance
“…Of importance is the finding that the NLRP1 inflammasome was present in motor neurons of the spinal cord, indicating that neurons express an inflammatory complex. 6 Similar findings regarding inflammasome activation in neurons have been obtained after traumatic brain injury 5,74 and stroke. 4 Increased levels of NLRP1, ASC, and caspase-1 have also been reported in the CSF of traumatic brain injury patients and are associated with poor prognosis.…”
Section: Inflammasome Activation After Brain and Spinal Cord Injurysupporting
confidence: 67%
See 2 more Smart Citations
“…Of importance is the finding that the NLRP1 inflammasome was present in motor neurons of the spinal cord, indicating that neurons express an inflammatory complex. 6 Similar findings regarding inflammasome activation in neurons have been obtained after traumatic brain injury 5,74 and stroke. 4 Increased levels of NLRP1, ASC, and caspase-1 have also been reported in the CSF of traumatic brain injury patients and are associated with poor prognosis.…”
Section: Inflammasome Activation After Brain and Spinal Cord Injurysupporting
confidence: 67%
“…13 In this regard, immunoprecipitation experiments indicate protein-protein interactions are made between NLRP1, ASC, caspase-1, caspase-11, and XIAP in neuronal lysates of sham and spinal cord-injured and brain-injured rodents. 5,6 These studies indicate that the inflammasome components in the CNS are preassembled before activation; however, it is possible that additional inflammasome proteins are recruited into inflammasome complexes as the inflammatory response becomes exacerbated. It has been suggested that preassembly of inflammasome complexes in CNS cells facilitates a rapid triggering of the innate immune response after CNS trauma.…”
Section: The Nlrp1 Inflammasomementioning
confidence: 99%
See 1 more Smart Citation
“…Caspase-1 then processes pro-IL-1β to a mature form that is rapidly secreted from the cell (5). The activation of caspase-1 can also cause cell death (6).…”
mentioning
confidence: 99%
“…TLRs induce transcriptional activation of pro-IL-1β, which is proteolytically processed via inflammasome activation (16,17). Studies have shown that neutralization of inflammasome activity results in less severe tissue pathologies following thromboembolic stroke (18,19). Currently, the exact function, complex molecular mechanisms, and precise interaction between TLRs and inflammasomes in the development of retinal ischemic injury remain elusive.…”
mentioning
confidence: 99%